2023
DOI: 10.31223/x55080
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Statistical Evaluation of Seismic Velocity Models of Permafrost

Abstract: The warming climate in high-latitude permafrost regions is leading to permafrost degradation. Estimating seismic velocity in permafrost can help predict the geomechanical properties of permafrost and provide information for planning and designing resilient civil infrastructure in cold regions. Seismic velocities of permafrost are mainly influenced by three components in permafrost: soil grains, water, and ice. Unfrozen water content reflects the variation of ice content and therefore is a key parameter in pred… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 55 publications
2
7
0
Order By: Relevance
“…A low-high-low velocity pattern is evident in all models, indicating the active layer and transitional zone (with low velocity), ice-rich permafrost (with high velocity), and partially frozen permafrost with scattered ice (low velocity). Previous studies have shown a strong correlation between permafrost temperature and V s (Ji et al, 2023;Kurfurst, 1976;Nakano et al, 1972). The low-high-low velocity pattern is consistent with the general trend of permafrost temperature variation with depths, as in a previous study (Smith et al, 2022).…”
Section: Site Characterization Of Disturbed and Undisturbed Permafrostsupporting
confidence: 90%
See 4 more Smart Citations
“…A low-high-low velocity pattern is evident in all models, indicating the active layer and transitional zone (with low velocity), ice-rich permafrost (with high velocity), and partially frozen permafrost with scattered ice (low velocity). Previous studies have shown a strong correlation between permafrost temperature and V s (Ji et al, 2023;Kurfurst, 1976;Nakano et al, 1972). The low-high-low velocity pattern is consistent with the general trend of permafrost temperature variation with depths, as in a previous study (Smith et al, 2022).…”
Section: Site Characterization Of Disturbed and Undisturbed Permafrostsupporting
confidence: 90%
“…Investigating the long‐term effect of civil infrastructure on permafrost’s stiffness could help improve the engineering design of structures’ foundations on permafrost. Permafrost’s parameters, such as V S 30 and E, are affected by soil types (Coduto, 1999), soil temperature (Ji et al., 2023), and soil’s ice content (Fisher et al., 2020). Changes in these soil properties show possible changes in soil types, thermal conditions, and cryostructure.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations